المشورة في الاندلس ابان امارة عبد الرحمن الداخل (138-172هـ/ 755-778م) - محمد جودي, احمد; عليوي كامل, عدوية (Journal of College of Education, 2020)
The Umayyad rule in the Levant ended after the success of the Abbasid revolution in 132 AH / 750 AD and the control of the Levant. The Abbasids did not settle for this victory, but followed a policy of violence and cruelty against the Umayyads, as Ibn Adhari recalls. Among the survivors was Abd al-Rahman ibn Mu'awiya, who went to North Africa from which he crossed into Andalusia.Before going into the political events in the era of the emirate and the accompanying advice summarized what the sources said about the features of the personality of Abdul Rahman, as it is useful to see them in relation to the subject of the study.Ibn Hayyan shows us some of the qualities of Abdul Rahman inside, saying: "Abdul Rahman Rajeh dream, firm knowledge, piercing understanding, many firm, resolute, fast-moving, connected to the movement, not immortal to rest, and not to let him, and do not eat things to Other then not unique in concluding his opinion "It is clear to us from this description, specifically the last paragraph of the text, that among the qualities of Abdul Rahman was that he adopted the principle of counseling. To participate in the drafting of the country's fateful decisions.In this study, we clarified the application of the principle of counseling on various aspects of life and the same political life between the years (138-172 AH / 755-778), which is the period during which Prince Abdul Rahman Al-Dakhl came to power in Andalusia, which was founded by the Umayyad Emirate in Andalusia.